FAKTA TUJUAN PEMBAKARAN PADA LAHAN GAMBUT DI KABUPATEN KUBU RAYA DAN KABUPATEN BENGKAYANG PROVINSI KALIMANTAN BARAT - Hadi, Ari Krisno; Kartika, Anna Syilviana; Manik, Sahat Irawan (Jurnal Kajian Lingkungan, 2014)
JICA in collaboration with the Ministry of Forestry is implementing for the development of the capacity of forest fire prevention, especially stakeholders in the planning and implementation of prevention village in the district which has 3 region with peat in Riau and West Kalimantan. Kubu Raya and Bengkayang regency as target districts in West Kalimantan province frequently experience land burning on area each year, which could be the cause of greenhouse gas emissions. The main factor for the cause of fires is human behavior in utilization land, although climatic and environmental conditions possible in the industry enlarge the possibility and fire intensity. The Objectives of this research in this program are to review the facts of land burned in two target districts in West Kalimantan. This research is implemented in 30 villages, in the two regencies from January 2014-May 2014. The research Methods used is quantitative analysis using questionnaire. The results of the study that should be considered in prevention are: (1) the respondents burn the land in terms of farming, especially clearing up after a period of fallow land, clearing land after the harvest, when to plant, weed eradication, non-agricultural activities, (2) Based on the purpose of burning with the commodities sought that farmers burn rice fields dominate, and (3) There are three combinations of purpose to burn with cultivated rice commodity is currently planted with a combination of eradicating pests, a combination of clean soil after harvest to eradicate pests and combination with clean soil when planting after fallow periods for the province of West Kalimantan and Kubu Raya while Bengkayang is a rice and annual crops.Keywords: Fires, Biomass Burning Behavior, Climate Change Mitigation